Overcoming school violence: challenges and potential of UNESCO associated schools in Brazil, Canada and Mozambique - Guimarães-Iosif, Ranilce (2016)
UNESCO Associated Schools (ASPnet) hold great potential for addressing issues of violence whether at the school or community level or beyond. This study of ASPnet schools in Brazil, Canada and Mozambique suggests that these schools’ focus on strengthening the mechanisms of democracy, inclusive citizenship, and conflict transformation that creates a particularly effective dialogic space for critically and collectively engaging with conflict. The study contextualizes the UNESCO ASPnet projects in relation to creating a culture of peace, provides current data collected through interviews with over 100 school teachers, administrators, parents and students. The investigation suggests that UNESCO ASPnet schools provide ways of overcoming violence and transforming conflict through attention to human rights, democracy, respect for diversity, and global perspectives on sustainability and world issues.